2016
DOI: 10.1097/brs.0000000000001182
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Correction in Patients With Lenke 1 Adolescent Idiopathic Scoliosis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Two studies in 2016 showed support for a positive correlation between coronal curve correction and anchor density. Ketenci et al [15] studied 76 matched Lenke 1 patients and equally divided these patients into the consecutive pedicle screw group (mean anchor density 2) and the interval pedicle screw group (mean anchor density 1.14). A significantly better coronal and rotational correction of thoracic curve was observed in the consecutive pedicle screw group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies in 2016 showed support for a positive correlation between coronal curve correction and anchor density. Ketenci et al [15] studied 76 matched Lenke 1 patients and equally divided these patients into the consecutive pedicle screw group (mean anchor density 2) and the interval pedicle screw group (mean anchor density 1.14). A significantly better coronal and rotational correction of thoracic curve was observed in the consecutive pedicle screw group.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining adequate lumbar lordosis is also essential to balanced sagittal profiles in long-segments instrumented spinal surgery [26]. Larson et al [13] found high anchor density was associated with postoperative hypokyphosis in Lenke 1,2 AIS patients, while several other studies reported no correlations between anchor density and thoracic kyphosis/lumbar lordosis correction [14, 15, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedicle screw construct systems have been increasingly popular for treating patients with spinal deformities, [ 4 7 ] and a significant correlation between the implant density and major curve correction has been reported [ 8 10 ]. However, substantial research has shown that low density (LD) screw constructs can provide similar radiographic and clinical outcomes [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this article is to describe the innovative posterior one stage surgical technique summarized with the acronym Hi-PoAD, which consists of simultaneous application of different surgical strategies, all well described individually, as high-density screwing [6][7][8][9], Ponte osteotomies [10][11][12][13], asymmetric rods contouring [14][15][16], direct vertebral rotation (DVR) [17] in the treatment of rigid AdIS (with less than 25% of correction at bending supine radiographs), the complication rate and the clinical and radiographical results obtained at minimum 2 years follow-up (FU) in a cohort of patients over 40 years treated.…”
Section: Introductionmentioning
confidence: 99%